2019
DOI: 10.4142/jvs.2019.20.e34
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of right pulmonary artery distensibility in dogs with pulmonary hypertension

Abstract: The right pulmonary artery distensibility (RPAD) index has been used in dogs with pulmonary hypertension (PH) caused by heartworm infection, myxomatous mitral valve disease, or patent ductus arteriosus. We hypothesized that this index correlates with the tricuspid regurgitation pressure gradient (TRPG) assessed by echocardiography and could predict survival in dogs with PH secondary to various causes. To assess this hypothesis, the medical records of 200 client-owned dogs at a referral institution were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Right ventricular function was significantly worse in dogs with PH not secondary to LHD when compared to dogs with PH secondary to LHD. However, survival times were not significantly different between dogs with PH secondary to LHD (ie, MMVD) and dogs Numerous studies have documented that RA enlargement (increased RAA), 19 RV enlargement (increased RVAd), 20 PA enlargement (increased PV/Ao), 7,14 and reduced RPAD index [14][15][16][17] are common in dogs with PH and that RV systolic dysfunction (reduced TAPSE) occurs in some dogs with PH. 21,22 Right ventricular enlargement and systolic dysfunction, PA enlargement or reduced RPAD index, and RA enlargement are considered to be clinically useful echocardiographic signs of PH and help assess the probability of PH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Right ventricular function was significantly worse in dogs with PH not secondary to LHD when compared to dogs with PH secondary to LHD. However, survival times were not significantly different between dogs with PH secondary to LHD (ie, MMVD) and dogs Numerous studies have documented that RA enlargement (increased RAA), 19 RV enlargement (increased RVAd), 20 PA enlargement (increased PV/Ao), 7,14 and reduced RPAD index [14][15][16][17] are common in dogs with PH and that RV systolic dysfunction (reduced TAPSE) occurs in some dogs with PH. 21,22 Right ventricular enlargement and systolic dysfunction, PA enlargement or reduced RPAD index, and RA enlargement are considered to be clinically useful echocardiographic signs of PH and help assess the probability of PH.…”
Section: Discussionmentioning
confidence: 97%
“…These measurements are largely based on characteristic cardiac changes that occur secondary to PH and have been previously evaluated in dogs diagnosed with PH. For example, the pulmonary artery might dilate, 7,14 exhibit reduced distensibility (quantified by the right pulmonary artery distensibility [RPAD] index), [14][15][16][17] or both. The blood flow profile in the pulmonary artery might exhibit a shortened acceleration time when indexed to ejection time (AT/ET).…”
Section: Introductionmentioning
confidence: 99%
“…34 Values < 30% indicated reduced RPAD and values < 22% were consistent with severe PH. 24,34,35 Tricuspid valve regurgitation (TR) and pulmonary valve regurgitation (PR) were recorded as present, absent, or in the case of TR, present but unable to be measured owing to the presence of intracardiac heartworms. Peak velocity of tricuspid (systolic timing) and pulmonary (early diastolic timing) valve regurgitation was measured when Doppler recordings were available.…”
Section: Echocardiographymentioning
confidence: 99%
“…Frequent follow-up, screening tests or treatment responses are needed clinically, so an alternative non-invasive method is desirable. [ 23 ] CTPA is now widely used in clinical practice. Many studies have demonstrated that this rapid, accurate, and non-invasive method can acquire embolism information for APE and also provide functional RV information.…”
Section: Discussionmentioning
confidence: 99%